2015
DOI: 10.1159/000373987
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear SMAD2 Restrains Proliferation of Glioblastoma

Abstract: Aims: Although TGFβ receptor signaling has been shown to play a role in regulation of the growth and metastasis of glioblastoma multiforme (GBM), the downstream pathway through either SMAD2 or SMAD3 has not been elucidated. In this study, we investigate whether nuclear SMAD2 can restrain the proliferation of glioblastoma. Methods: A total of 23 resected specimens from GBM patients were collected for SMAD2 detection. Human GBM cell line A172, U87mg, D341m and Hs683 were maintained in Dulbecco's modified Eagle's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In our previous study, we found that ALI induced phosphorylation of a key factor SMAD2 of TGF β receptor signaling [22][23][24][25][26][27][28], which could be dose-dependently inhibited by ACE2. Hence, it is possible that the regulation of miR-4262 by ACE2 could be through modulation of TGF β receptor signaling.…”
Section: In Vivo Administration Of As-mir-4262 Mimics the Effects Of mentioning
confidence: 99%
“…In our previous study, we found that ALI induced phosphorylation of a key factor SMAD2 of TGF β receptor signaling [22][23][24][25][26][27][28], which could be dose-dependently inhibited by ACE2. Hence, it is possible that the regulation of miR-4262 by ACE2 could be through modulation of TGF β receptor signaling.…”
Section: In Vivo Administration Of As-mir-4262 Mimics the Effects Of mentioning
confidence: 99%
“…Transforming growth factor β (TGFβ) receptor signaling pathways play essential and diverse roles in the regulation of many biological events, including cell replication, differentiation, apoptosis and tissue remodeling [7]. The well-established functional role of BMPs in development and their ability to regulate vital cellular processes have made them an increasingly interesting topic in cancer research, and a wealth of new information has been reported regarding the role of BMPs in cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most aggressive brain tumour in humans and is regulated by many different molecules [26,27]. The microenvironment of glioblastomas seems to be restricted when the expression of KIF14 is inhibited [28] or due to low doses given of curcumin [29].…”
Section: Introductionmentioning
confidence: 99%